From Worldview to Way of Life: Forming Student Dispositions toward Human Flourishing in Christian Higher Education. Issue 1 (May 2018) - Setran, David
While Christian college students often develop a worldview that emphasizes both individual and social flourishing for the Kingdom of God, there are a number of barriers that may prevent them from living lives committed to others' flourishing. In particular, many of their regular practices generate dispositions that lead in the direction of personal advancement, material security, and devotion to a narrow sphere of family and friends. The development of an others-focused Christian worldview may not be enough to combat these deeply rooted and self-focused dispositional tendencies. Instead, faculty, staff, and mentors must recognize the importance of students' spiritual practices and the ways these can develop inclinations that both foster commitments to others' flourishing and combat the self-focused dispositions that block such commitments. This article highlights some of those practices and addresses the ways in which these can help bridge the gap between students' worldviews and their concrete "ways of life."